Findings from a Qualitative Needs Assessment of Equal Access Birmingham, a Student-Run Free Clinic in the Southern United States - Chilukuri, Pranaya; Williams, Collier; Dowla, Shima; Paul, Shejuti; Sheets, Lindsay; Zinski, Anne; Van Wagoner, Nicholas (Journal of Student-Run Clinics, 2021)
Background: Student-run free clinics (SRFCs) are becoming increasingly common across the United States. To better understand clientele and improve these organizations, it is important to assess patient feedback about SRFC services. This study is based on Equal Access Birmingham (EAB), a SRFC that aims to provide and improve quality healthcare for underserved populations in central Alabama. A qualitative needs assessment of patients receiving care at EAB has not yet been performed. The purpose of this study was to identify and explore EAB clients’ perceived health needs, health-related behaviors, and access to healthcare. Methods: Clients were recruited to participate in semi-structured qualitative interviews at EAB. Major themes included barriers to healthcare, primary health concerns, individual health behaviors, and patterns of clinic utilization. Results: The study analyzed 16 patient interviews. Participants stated that cost, transportation, and housing were barriers to healthcare. Their main health concerns were hypertension (cited by 21% of participants), diabetes (21%), pain (21%), and mental health management (21%). Ninety-four percent of study participants reported relying on EAB to obtain medication refills. Respondents also reported accessing the clinic for mental health issues, and many used EAB as their primary care provider. Conclusions: Despite numerous barriers, EAB was the source of primary healthcare and medications for many respondents. This qualitative investigation identified specific concerns and noteworthy strengths that may extend to other SRFCs.